Sugar Content, Crude Fiber Content, Antioxidant Activity, and Sensory Characteristics Of Sorghum (Sorghum Bicolor (L.)Moench) Snack Bar with Addition Of Klutuk Banana (Musa Balbisiana Colla) Flour - Setyaningtiyas, Tika; Fitriyanti, Addina Rizky; Latrobdiba, Zahra Maharani; Sya'di, Yunan Kholifatuddin (Universitas Airlangga, 2024)
Sorghum and klutuk banana can be utilized as functional foods that are high in fiber and antioxidant and suitable for diabetic people. This study examined the effects of klutuk banana flour on the sugar content, crude fiber content, antioxidant activity, and sensory characteristics of sorghum snack bars. This study is true experimental, employing a completely randomized design (CRD) with 4 formulations: the ratio of sorghum and banana flour klutuk PO (100:0), P1 (90:10%), P2 (80:20%), and P3 (70:30%), and 6 repetitions. Sugar content, crude fiber, and antioxidant activity were observed and analyzed using the one-way ANOVA (Analysis of Varian) test, followed by Duncan test. The sensory properties were evaluated using Friedman test. 1.94–2.86% sugar, crude fiber content is 46.04–70.89%, and antioxidant activity is 9.06–15.0%. The results revealed a significant relationship (p<0.05) between the addition of klutuk banana flour to the sorghum snack bar sugar level, crude fiber content, and antioxidant activity. Texture, color, flavor, and scent were not significantly affected by the addition of klutuk banana flour to sorghum snack bars. The optimal formulation of a sorghum snack bar with the inclusion of klutuk banana flour was discovered to be P3 based on the test sugar content, crude fiber content, antioxidant activity, and sensory characteristics. The nutritional value of the P3 formulation have met USDA (2018) standards for the Nutri-Grain Fruit and Nut Bar, but the sugar content have not meet the SNI 01-3702-1995 (Indonesian National Standards) quality requirements for diabetes diet biscuit.